COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN BANK SAMPAH DI KOTA PEKANBARU PADA TAHUN 2021 - Devara Amelia Fadjri; Adlin Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Abstract Garbage is one of the problems experienced by almost all countries in the world. According to data from the National Waste Management Information System (SIPSN), the waste generation in 2021 in Indonesia will reach 30,881,803.15 Tons. Waste management can run effectively and efficiently if there is good cooperation from the government, society and the private sector. The waste bank exists as a form of collaboration between the government and the private sector to create a strategy for implementing 3R in waste management in Pekanbaru City. This research aims to find out the practice of collaborative governance in the management of waste banks in Pekanbaru City in 2021. Based on the results of this study, it was concluded that the implementation of a waste bank in Pekanbaru City in 2021 was welcomed by all actors and had a positive impact on waste management in Pekanbaru City. The Garbage Bank also generates profits seen from the large number of people participating in it. But in achieving innovation is less effective. This happens because of a lack of trust between stakeholders, lack of information sharing and coordination which causes innovation to not run effectively, and a lack of facilities and infrastructure needed in implementing a waste bank. Keywords: Collaborative Governance, Waste Bank Management